The Role of Digital Technology in Driving the Growth of Halal Fintech - Ali Masyhuri, Mohammad (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study explores the role of digital technology in driving the growth of the halal fintech sector, which is growing along with the increasing demand for sharia-compliant financial services. Digital technologies, especially blockchain, artificial intelligence (AI), and big data, enable halal fintech to provide more transparent, efficient, and inclusive services. The adoption of digital technology in the sharia financial sector increases accessibility and convenience for consumers, and supports the creation of a more sustainable financial ecosystem (Zohra et al., 2021). By leveraging digital platforms, halal fintechs are not only strengthening their business foundations but also playing a vital role in expanding financial inclusion in countries with Muslim-majority populations. This study provides insights into how digital transformation can catalyze the growth of the halal fintech sector, while addressing the challenges faced by the industry in ensuring compliance with sharia principles.